Indonesia Parliamentary Diplomacy: The Leadership of House Representatives Republic of Indonesia in ASEAN Inter- Parliamentary Assembly (AIPA) 2011- 2012 - Firdaus, M. Jullyo Bagus; Kresnawati, Megahnanda Alidyan (WIMAYA, 2021)
This paper discusses the implementation of Indonesian parliamentary diplomacy when Indonesia became the leader of the ASEAN Inter-Parliamentary Assembly (AIPA) (2011-2012). In the same period, Indonesia also assumed the chairmanship of the Association of Southeast Asian Nations (ASEAN). Developed from the concept of multi-track diplomacy and total diplomacy, the authors highlight how the House of Representatives of Republic Indonesia (DPR-RI) plays a role in a track 11⁄2 diplomacy. The authors argue that DPR-RI's active participation is essential to oversee national compliance on international legal norms and rules through the case of AIPA.